(untitled) (Journal Of Educational and Psychological Researches, 2015)
This study aimed to identify the educational leadership in the light of my theory xy and its relationship to the morale of the managers of the junior high school as the study population consisted of directors of junior high school in the city of Baghdad of six directorates education for the academic year 2013-2014 AD The number of managers (211) as director, and amounted to a sample Search of (150) director and director of the research community overall rate (71%) and represent this community fully representative sample, two tools were used in the study: the first measure of educational leadership in the light of my theory xy and the second tool to gauge morale. Results concluded that the prevailing leadership style of principals came in the light of the theory y. As well as the results showed that the morale of good managers. And appeared as well as the existence of a correlation between educational leadership in the light of the theory of y and morale The researcher recommends carefully Education Directorates views and proposals prep school principals and make Education Directorates more attention towards the application of modern management methods, thus contributing to the improvement of educational leadership style in junior high school. The researcher proposes to conduct a similar study and its relationship with other variables such as organizational loyalty or job satisfaction